Oxidation state of a polyurethane membrane after plasma etching - Moles, Matthew D.; Scotchford, Colin A.; Campbell Ritchie, Alastair (Hindawi, 2014)
Low moduli cell culture substrates can be used to apply dynamic mechanical strain to cells, by surface deformation. Understanding the surface interaction with cells is critical to improving cell adhesion and normal growth. A medical grade polyurethane (PU), Chronoflex AL 80A, was modified by oxygen plasma etching and characterised by X-ray photoelectron spectroscopy. Etching resulted in increased cross-linking at the isocyanate bond and formation of new oxygen moieties. The model, derived from patent data and XPS data of the unetched PU, indicated that the additional oxygen was likely to be hydroxyl and carbonyl groups. Etched membranes enhanced protein adhesion, resulting in full surface coverage compared to unetched PU. The etched PU supported cell adhesion and spreading, while the unetched PU was not conducive to monolayer formation.